PARADIGM EDUCATIONAL INFORMATION ENVIRONMENT FORMATION IN THE TECHNICAL HIGHER EDUCATIONAL INSTITUTIONS - Рахманов, Віталій Олегович (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In article identified and analyzed paradigm educational information environment formation in the technical higher educational institutions. Considered a paradigm based on the basis of humanitarization and humanization of higher education. They aim to provide valuable guidance and motivation to establish criteria for the selection of a professional field to create conditions for self-development and personal fulfillment. Revealing the integrity of character education and regulating scientific, research and practical innovation training activities educational paradigm should be considered in conjunction. Therefore, analysis of the dynamics of formation and development paradigms helps to preserve the principles of learning, performs genetic nucleus of the national pedagogical science and practice